Relationship between serum CHIP levels with cardiovascular disease in maintenance haemodialysis patients. (27th March 2023) - Xu, Taijing; Liu, Mengjun; Zhao, Xinhui; Zhang, Shenglei; Ma, Shuchen; Wang, Jun; Wang, Yi; Guo, Yide; Wang, He; Hong, Xuan; Liu, Feng
Abstract: Many preclinical studies reported that the carboxyl terminus of Hsp70‐interacting protein (CHIP) has cardiovascular protective effects. This study was designed to explore whether CHIP is related with cardiovascular disease (CVD) in maintanence haemodialysis (MHD) patients. 217 MHD patients and 150 healthy controls were recruited, serum CHIP concentration and clinical characteristics were measured. MHD patients were followed‐up for 36 months and their cardiovascular events (CVEs) and survival conditions were recorded. Here, the data shows that serum CHIP concentrations in MHD patients were lower than those in healthy controls (31.69 ± 18.2 pg/mL vs 84.53 ± 22.1 pg/mL, p < 0.05). CHIP negatively correlated with age, C‐reactive protein, B‐type brain natriuretic peptide, phosphorus, parathyroid hormone, carotid intima‐media thickness (CIMT) and left ventricular septal thickness (LVSTd), whereas it positively associated with albumin, haemoglobin, creatinine, Kt/V and ejection fraction ( p < 0.05, respectively). Partial correlation and multiple linear regression analysis verified the negative relationship between CHIP with CIMT or LVSTd ( p < 0.05, respectively). Using quartile method and Kaplan–Meier survival function, it indetified that the lower serum CHIP concentration predicted risk of CVEs, CVD and all‐cause death ( p < 0.001). Cox regression analysis manifested CHIP was negatively associated with CVEs (HR = 0.914, 95%CI 0.880–0.950, p < 0.001), CVD mortality (HR = 0.747, 95%CI 0.651–0.857, p < 0.001) and all‐cause death (HR = 0.769, 95%CI 0.696–0.850, p < 0.001). In conclusion, the data of this study revealed that serum CHIP level is significantly correlated with multiple risk factors of CVD and may be one of the predictors of CVD risk and death in MHD patients. Abstract : Serum CHIP level is significantly correlated with multiple risk factors of cardiovascular disease (CVD) and may be one of the predictors of CVD risk and death in maintenance haemodialysis (MHD) patients.